1994
DOI: 10.1002/ijc.2910570214
|View full text |Cite
|
Sign up to set email alerts
|

Quercetin enhances transforming growth factor β1, secretion by human ovarian cancer cells

Abstract: Our study demonstrates that quercetin (Q)-induced growth-inhibitory activity in ovarian cancer cells may be mediated by modulation of transforming growth factor beta 1 (TGF beta 1) production. We used the OVCA 433 cell line which is very sensitive to the anti-proliferative effect of Q and expresses high-affinity, low-capacity TGF beta 1 receptors. Conditioned medium (CM) from Q-treated cells is able to displace 125I-TGF beta 1 from binding to its receptor; moreover Q (10 microM) increases TGF beta 1 activity i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(18 citation statements)
references
References 19 publications
0
18
0
Order By: Relevance
“…Both, quercetin 3-O-β-galactoside (10) and quercetin 3-O-α-arabinoside (9) are able to inhibit lung large cell carcinoma proliferation with IC 50 values of 3.2 and 7.5 μg ml -1 , respectively. Several studies have been done on fl avonoids' antiproliferative effects against human ovarian, leukemic, intestinal, lung, breast and bladder cancer cells (Scambia et al, 1994;Agullo et al, 1997;Narayanan et al, 1999;Uddin and Choudhry, 1995).…”
Section: Resultsmentioning
confidence: 99%
“…Both, quercetin 3-O-β-galactoside (10) and quercetin 3-O-α-arabinoside (9) are able to inhibit lung large cell carcinoma proliferation with IC 50 values of 3.2 and 7.5 μg ml -1 , respectively. Several studies have been done on fl avonoids' antiproliferative effects against human ovarian, leukemic, intestinal, lung, breast and bladder cancer cells (Scambia et al, 1994;Agullo et al, 1997;Narayanan et al, 1999;Uddin and Choudhry, 1995).…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that in some type of cancer cells, the antiproliferative effect of quercetin is mediated by TGF-␤1. Thus, quercetin induces a release of TGF-␤1 that acts in an autocrine manner inhibiting cell growth (39,40). Because TGF-␤1 inhibits growth in several thyroid culture cells including FRTL-5 through phosphorylation of Smad proteins (41-43), we investigated whether this was the mechanism involved in the quercetin antiproliferative effect.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that one of the mechanisms by which quercetin suppress growth in cancer cells is through an increase of TGF-␤1 activity (39,40). This increase is time de- pendent (starting after 4 h of treatment and reaching a maximum after 24 h) and occurs at a posttranscriptional level.…”
Section: Signal Pathways Involved In Frtl-5 Cells Growth Inhibition Bmentioning
confidence: 99%
“…Quercetin is the most widely distributed flavonoid, found in apples, onions, black tea and red wine [9] . Studies in vitro and in vivo have suggested that quercetin may have a protective role against colon [10][11][12] , breast [13] and ovarian [14] cancers.…”
Section: Introductionmentioning
confidence: 99%